Persoalan Pengudusan Pasangan dalam Pernikahan Beda Agama: Kritik Sosio-Historis 1 Korintus 7:12-16 - Vincent Kalvin Wenno (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Abstract. This study describes the marriage legality between Christian and non-Christian in Corinth. The text that is used as a focus for interpretation is 1 Corinthians 7:12-16, by using the socio-historical criticism. The text was chosen because it talked about the marriage of different beliefs that took place in the City of Corinth. To interpret text by the socio-historical criticism, things to consider are: First, the background of the social and historical context and mixed marriage in Corinth. Second, the problem of holiness and divorce in marriage in Corinth. Based the study, it can be explained that Paul's understanding of the sanctity of Christian marriage is a way to make a border between holiness and unholiness in pluralistic Corinthian society.Abstrak. Tulisan ini menguraikan persoalan keabsahan pernikahan antara orang Kristen dan bukan Kristen di Kota Korintus. Fokus teks yang menjadi acuan penafsiran adalah 1 Korintus 7:12-16, dengan menggunakan pendekatan tafsir sosio-historis. Teks tersebut dipilih karena berbicara menyangkut pernikahan berbeda keyakinan yang terjadi di Kota Korintus. Untuk menafsirkan teks dengan sosio-historis, maka hal yang diperhatikan adalah latar belakang konteks sosial-historis dan pernikahan campuran di Korintus, serta masalah kekudusan dan perceraian dalam pernikahan di Korintus. Berdasarkan hasil studi, maka dapat dijelaskan bahwa pemahaman Paulus tentang kudusnya pernikahan Kristen adalah cara menarik batas antara kudus dan cemar dalam masyarakat Korintus yang majemuk.